2007
DOI: 10.1097/01.sga.0000287204.44226.7e
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Modification Counseling in Patients With Gastroesophageal Reflux Disease

Abstract: The purpose of this study was to determine the rate of documented counseling on lifestyle modifications in patients presenting to the primary care setting with a diagnosis of gastroesophageal reflux disease. Retrospective chart review was conducted for 502 active patients with a primary or secondary diagnosis of gastroesophageal reflux disease from two internal medicine clinics at the University of Kansas School of Medicine-Wichita. Charts were reviewed for documented counseling on four specific lifestyle modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Although these management strategies are low cost and effective, prior studies have demonstrated that provider adherence to delivering recommendations is suboptimal. 10,11 …”
Section: Initial Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these management strategies are low cost and effective, prior studies have demonstrated that provider adherence to delivering recommendations is suboptimal. 10,11 …”
Section: Initial Approachmentioning
confidence: 99%
“…6 However, there is limited data on the prognostic utility of impedance monitoring in patients undergoing evaluation for anti-reflux surgery. 710 Wireless pH monitoring facilitates prolonged monitoring for up to 96 hours without a transnasal catheter, and may increase the sensitivity of reflux detection. 11, 12 Currently the optimal diagnostic strategies utilizing pH monitoring remains an area of substantial controversy amongst clinicians.…”
Section: Diagnostic Testing and Endoscopic Interventionsmentioning
confidence: 99%
“…As Vemulapalli 1 reports in this issue of Nutrition in Clinical Practice (NCP), only 12% of patients with gastroesophageal reflux disease (GERD) who were surveyed in one study received dietary advice from their doctor. 2 Patients assume that diet is a factor in the disease process and generation of symptoms. In a survey of patients with irritable bowel syndrome (IBS), 65% indicated that food clearly triggered their symptoms.…”
Section: Food For Thought Should Lead To Food For Therapymentioning
confidence: 99%
“…Although effective weight management in the care of GERD is a national priority, implementing clinically feasible and effective interventions is challenging 9 . A multitude of factors influence the effectiveness of weight loss interventions.…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of factors influence the effectiveness of weight loss interventions. Health system barriers include provider time constraints, insufficient reimbursement, and inadequate provider training 9,10 . In addition, patient engagement is influenced by choices, attitudes, and beliefs; as such effective interventions need to focus on changeable behaviors and objectives 911 .…”
Section: Introductionmentioning
confidence: 99%